2018
DOI: 10.1093/toxsci/kfy062
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Manganese Exposure Impairs Neurogenesis in the Adult Rat Hippocampus

Abstract: Adult neurogenesis takes place in the brain subventricular zone (SVZ) in the lateral walls of lateral ventricles and subgranular zone (SGZ) in the hippocampal dentate gyrus (HDG), and functions to supply newborn neurons for normal brain functionality. Subchronic Mn exposure is known to disrupt adult neurogenesis in the SVZ. This study was designed to determine whether Mn exposure disturbed neurogenesis within the adult HDG. Adult rats (10 weeks old) received a single dose of bromodeoxyuridine (BrdU) at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 97 publications
2
7
0
Order By: Relevance
“…Consistently, studies from other laboratories have also found that NSCs are the prime targets of Mn toxicity in both the DG and the SVZ [20]. These NSCs are stem celllike precursors that exist, predominantly, in these two brain regions to produce somatic cells such as neurons and glial cells in response to a variety of environmental conditions [20]. Furthermore, converging evidence has shown that NSCs in the brain undergoing differentiation and maturation play important roles in learning and memory functions [19,21], suggesting the potential of NSC transplantation as a promising tool to compensate for neuronal loss and structural damage in the adult hippocampus [20].…”
supporting
confidence: 81%
See 4 more Smart Citations
“…Consistently, studies from other laboratories have also found that NSCs are the prime targets of Mn toxicity in both the DG and the SVZ [20]. These NSCs are stem celllike precursors that exist, predominantly, in these two brain regions to produce somatic cells such as neurons and glial cells in response to a variety of environmental conditions [20]. Furthermore, converging evidence has shown that NSCs in the brain undergoing differentiation and maturation play important roles in learning and memory functions [19,21], suggesting the potential of NSC transplantation as a promising tool to compensate for neuronal loss and structural damage in the adult hippocampus [20].…”
supporting
confidence: 81%
“…We and others have previously detected a decrease in the proliferation of multipotent neural stem cells (NSCs) within the hippocampal SGZ that was suggestive of disrupted neurogenesis that closely coincided with deficits in spatial recognition. Consistently, studies from other laboratories have also found that NSCs are the prime targets of Mn toxicity in both the DG and the SVZ [ 20 ]. These NSCs are stem cell-like precursors that exist, predominantly, in these two brain regions to produce somatic cells such as neurons and glial cells in response to a variety of environmental conditions [ 20 ].…”
supporting
confidence: 79%
See 3 more Smart Citations